2015
DOI: 10.3102/1076998615606113
|View full text |Cite
|
Sign up to set email alerts
|

Stan

Abstract: Stan is a free and open-source Cþþ program that performs Bayesian inference or optimization for arbitrary user-specified models and can be called from the command line, R, Python, Matlab, or Julia and has great promise for fitting large and complex statistical models in many areas of application. We discuss Stan from users' and developers' perspectives and illustrate with a simple but nontrivial nonlinear regression example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
138
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 444 publications
(139 citation statements)
references
References 12 publications
1
138
0
Order By: Relevance
“…Finally, recent research (Alvarez et al, 2014) has revealed that the scaled inverse Wishart distribution (O'Malley & Zaslavsky, 2008) and hierarchical half-t prior distribution proposed by Huang and Wand (2013) are less informative than the inverse Wishart, although they experience similar issues, albeit at a lesser scale (Alvarez et al, 2014). We do not believe we have completely resolved this issue, and recent advances in Bayesian methods (Gelman, Lee, & Guo, 2015) may further our understanding. Finally, our simulations indicate that specifying hyperpriors for the components of a covariance matrix is significantly more effective than using the inverse Wishart distribution, or other recently developed approaches (Huang & Wand, 2013;O'Malley & Zaslavsky, 2008) for capture-mark-recapture and other demographic analyses, as the hyperprior approach leads to accurate estimates of process correlations and variances given sufficient sample sizes.…”
Section: Implications For Future Researchmentioning
confidence: 81%
“…Finally, recent research (Alvarez et al, 2014) has revealed that the scaled inverse Wishart distribution (O'Malley & Zaslavsky, 2008) and hierarchical half-t prior distribution proposed by Huang and Wand (2013) are less informative than the inverse Wishart, although they experience similar issues, albeit at a lesser scale (Alvarez et al, 2014). We do not believe we have completely resolved this issue, and recent advances in Bayesian methods (Gelman, Lee, & Guo, 2015) may further our understanding. Finally, our simulations indicate that specifying hyperpriors for the components of a covariance matrix is significantly more effective than using the inverse Wishart distribution, or other recently developed approaches (Huang & Wand, 2013;O'Malley & Zaslavsky, 2008) for capture-mark-recapture and other demographic analyses, as the hyperprior approach leads to accurate estimates of process correlations and variances given sufficient sample sizes.…”
Section: Implications For Future Researchmentioning
confidence: 81%
“…We fit this model using Stan [25] with a uniform (improper) prior on the entries of B and T. The treatmentassociated mutational signature N was calculated from a point estimate of T as:…”
Section: Mutational Signaturesmentioning
confidence: 99%
“…We chose β 1 ∼ N (0, 1) for the (standardized) predictors. This prior is listed as a recommended 'generic weakly informative prior' in the Stan manual (Betancourt, Vehtari, & Gelman, 2015), and has been used in this context before (e.g., Gelman, Lee, & Guo, 2015).…”
Section: Statistical Modelsmentioning
confidence: 99%